Synthesis of Strontium Based on Natural Iron Sand North Lombok Coastal Club Doping Co and Cu Metal Ions As Power Generating Materials - Susilawati; Aris Doyan; Saprizal Hadisaputra; Lalu Muliyadi (Postgraduate, University of Mataram, 2023)
The SrCl2 with natural iron sand is the basic material for making Strontontium M-Hexaferrite (SrM) as a generator of electricity in the form of permanent magnets samples which are doped to make the utilization of SrM more effective by adding metal ions that have almost the same size as cobalt (Co) and cupper (Cu) using the coprecipitation method. The synthesis process was carried out in the chemical laboratory of the FKIP, the Highway Engineering Laboratory, the Faculty of Engineering and the advanced Biology Laboratory of the FMIPA UNRAM. In this study, concentration variations and temperature variations were used during the calcination process, namely (x = 0.0; 0.4; 0.8 and 1.0) (T = 800; 1000 and 1100 0C). These variations greatly affect the sample, where the greater the concentration and calcination temperature, the darker the resulting color in the sample and this is in accordance with the purpose of the calcination process, namely the greater the temperature at the time of calcination, the higher the water content in the sample reduced because the solvent in the sample evaporates. In addition to these materials, the solvent used also plays an important role in the process of making samples, namely using 25% HCl to dissolve, 37% NaOH so that the precipitation process is faster and distilled water as a neutralizer.